Influence of post-HIP temperature on microstructural and optical properties of pure MgAl2O4 spinel: From opaque to transparent ceramics. Issue 16 (December 2017) - Gajdowski, Caroline; Böhmler, Judith; Lorgouilloux, Yannick; Lemonnier, Sébastien; d'Astorg, Sophie; Barraud, Elodie; Leriche, Anne
Abstract: Transparent MgAl2 O4 spinel ceramics were processed from sub-micrometric commercial powder by applying a two-step procedure: pressureless sintering under vacuum followed by hot isostatic pressing. To limit grain growth and to avoid secondary reactions or impurities, no additives or sintering aids were added to the powder. First, pressureless sintering at 1500 °C during 2 h under vacuum led to opaque samples due to a high level of porosity. To improve the optical quality of the MgAl2 O4 ceramics and the in-line transmission in the visible range, a post-treatment by hot isostatic pressing was applied. Highly transparent ceramics were obtained after a post-treatment at 1800 °C for 10 h with an in-line transmission of 81% at 400 nm and 86% from 950 to 3000 nm for a thickness of 2 mm (98.8% of the theoretical transmission).